First Record of the Order Choanoflagellida in Turkey - Varol, Memet; Bekleyen, Aysel; Sen, Bulent; Gokot, Bulent (Central Fisheries Research Inst, 2011)
We report the first record of the order Choanoflagellida in the waters of Turkey. The choanoflagellate Salpingoeca amphoridium James-Clark was found in plankton net samples in November and December 2008, and January 2009 from the Batman Dam Lake, the Batman Stream and Hasankeyf sampling site of the Tigris River. Salpingoeca amphoridium was found attached to planktonic diatom Aulacoseria granulata (Ehrenberg) Simonsen.
Türkiye'deki Choanoflagellida ordosunun İlk kaydı
Keywords: Choanoflagellida; Salpingoeca amphoridium; new records; Turkey